The house in Norham Gardens - Lively, Penelope, 1933- (London : Jane Nissen Books, 2004)
The carved shield she finds in the attic, brought from New Guinea years ago, causes fourteen-year-old Clare disturbing dreams.
7.2
Young Adult.
Young Adult
Keywords: Space and time -- Fiction; Space and time -- Fiction; England -- Fiction; England -- Fiction